Rancang Bangun Sistem Pendeteksi Kondisi Ideal Fermentasi Kimchi berdasarkan pH dan Suhu menggunakan Metode Fuzzy Mamdani - Andre Rizki Haryuaditya; Mochammad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Kimchi is one of the processed vegetable foods that can change the selling price of vegetables. Kimchi is a traditional pickled vegetable originating from Korea. Many Indonesian people like to make kimchi and eat kimchi because kimchi is a food that is rich in probiotic bacteria and has Indonesian culinary flavors. Currently, the process of making kimchi fermentation is still done manually, thus affecting the conditions of kimchi fermentation. If the fermentation container is often opened, then air from outside will enter and cause temperature changes. If there is a significant change in temperature, the performance of the bacteria that carry out the fermentation process will be disrupted. Based on these problems, a detection system for the ideal conditions of kimchi fermentation based on pH and temperature was made using the fuzzy Mamdani method. The Mamdani fuzzy calculation process is assisted by the Embedded Fuzzy Logic Library (eFLL), which processes data input from the DHT11 temperature and pH sensors SEN0161-V2 based on the ESP32 Devkit V1 Microcontroller. After that, the system output will be displayed on a 16x2 LCD screen and an android application with Bluetooth communication. Based on sensor testing, the MAPE value of the pH sensor SEN0161-V2 is 1.81% with an accuracy of 98.19%, and the MAPE value of the DHT11 temperature sensor is 1.51% with an accuracy of 98.49%. Mamdani fuzzy algorithm testing is carried out every day for six days of fermentation by recording ten system output data to obtain a total of 60 test data. As a result, the MAPE value of the Mamdani fuzzy algorithm was obtained at 0.96% with an accuracy of 99.04% and an average computation time of 25.138.5 microseconds or 25 milliseconds.